Benefits of Lavender Aromatherapy in Reducing Menstruation Pain in Teenage Women - Ika Nur Saputri; Sari, Mayang (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
Adolescence is a transition stage that causes physical, emotional, and psychological changes. A disorder that often occurs in young women is menstrual pain which can change a woman's emotions in a short time, disrupting her routine and learning process. Aromatherapy can be applied directly through direct massage on the skin using plant extracts. Aromatherapy can treat respiratory problems, and pain, and reduce stress levels. Lavender oil is rich in analgesic essentials which can stimulate the nervous system to bring a feeling of calm to pain sufferers. The main aim of the research was to see how to reduce pain intensity in teenagers before and after being given lavender aromatherapy. The objective of implementing this PkM activity is so that young women at SMA Negeri 1 Perbaungan can experience increased knowledge and be able to carry out appropriate treatment for menstrual pain through the use of lavender aromatherapy. PkM activities were conducted through socialization, where the participants were young women at SMA Negeri 1 Perbaungan, totaling 30 participants. The PkM results show that many young women's menstrual pain conditions change from severe pain to mild and moderate pain after being given lavender aromatherapy therapy. This proves that giving lavender aromatherapy can reduce menstrual pain in young women. Apart from that, the socialization of PkM has been proven to be able to increase the knowledge of young women in understanding and applying it when menstrual pain occurs.